PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT TRI SARANA NUSANTARA DEPOK PANCORAN MAS - Dian Nurmala Sari; Maghfiroh Yanuarti (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the partial and simultaneous effect of work discipline and physical work environment on employee performance at PT Tri Sarana Nusantara. The population and sample of this study amounted to 80 respondents with a saturated sampling technique. Methods of data analysis using validity test, reliability test, classic assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test and hypotesis testing. The results showed that (1) There is a Partial Effect of Work Discipline On Employee Performance at PT Tri Sarana Nusantara, a simple linear regression equation Y =12.153 + 0,726 (X1), the coefficient correlation result is 0.645, the influence contribution is 41,6%, as well as the test the hypothesis shows that the tcount is 3.173 > ttable 1.990 and or the sig value is 0.002 <0.05. (2) There is a partial effect of the physical work environment on employee performance at PT Tri Sarana Nusantara, a simple linear regression equation Y = 19.930 + 0,570 (X2), a coefficient correlation result of 0,728, a contribution of 53% and the hypothesis test shows a tcount value of 5.586 > ttable 1.990 and or a sig value of 0.000 <0.05. (3) There is a Simultaneous Effect of Workload and Physical Work Environment on Employee Performance at CV Elza Mandiri Bogor Regency, a multiple linear regression equation Y =11,168 + 0,342(x1) + 0,418(x2), a correlation result of 0,764, a contribution of 58,4%, and simultaneous hypothesis testing shows an Fcount of 54.096 > Ftable of 3.111 and or a sig value of 0.000 <0.05